Potential activities to reduce the extent of substandard and falsified antibiotics across Africa and associated antimicrobial resistance - Maluleke, Tiyani Milta; Mekonnen, Biset Asrade; Ubaka, Chukwuemeka Michael; Paramadhas, Bene D. Anand; Munzhedzi, Mukhethwa; Kalungia, Aubrey Chichonyi; Hango, Ester; Kumar, Santosh; Godman, Brian; Meyer, Johanna C. (Frontiers in Tropical Diseases, 2025)
Antimicrobial resistance (AMR) is a global public health threat exacerbated by inappropriate antibiotic use. This is particularly important in Africa. The availability of substandard and falsified antibiotics, particularly among African countries, contributes to this adding to the burden of AMR. Poor monitoring and regulatory controls among African countries increases the public health risks of these antibiotics. This is especially the case in the informal sector. Addressing Africa’s battle against substandard and falsified antibiotics requires an integrated approach building on current WHO, Interpol and Pan-African initiatives. Activities include harmonizing regulatory activities across Africa and increasing the monitoring of available antibiotics as well as fines and sanctions for offenders. In addition, reducing the current high levels of inappropriate antibiotic use makes the market for falsified and substandard antibiotics considerably less attractive.